Methodos, Strategies, Techniques and Materials to Foster a Positive Coexistence in Schools - Díaz Pino, Alejandra Alexia; González Córcoles, María del Rosario (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2025)
This paper deals with one of the research lines on coexistence carried out by the group PREVyCON in collaboration with CES Don Bosco College. More specifically, it focuses on the HELP Project, a pedagogical proposal for the improvement of coexistence and school atmosphere. This study analyses the most relevant methodologies for promoting a positive coexistence in school, describes suitable techniques and materials that make possible their implementation in the students’ training.